Utilization and Conservation of Wild Plants by the Tribal Communities of Tripura - Malla, Suman; Shukla, Gopal; Chakravarty, Sumit (Indian Forester, 2012)
Plant gathering activities by the tribal communities of Tripura consist collection and conservation of 61 wild plant species for fruits, flowers, roots, tubers, stems, leaves, barks etc. This is primarily the responsibility of women but if necessary males render their help. The paper documents the various forest produces which are used as food, medicine, dye, aroma, etc. that form the part and parcel of unique pattern and choice of life style and the ways of conservation of these plants by the different tribal communities of Tripura.